A pilot survey on the assessment technique in accessing defects on heritage buildings in Malaysia / Nor Nadiah Ramli, Lilawati Ab Wahab and Haryati Mohd Isa - Ramli, Nor Nadiah; Ab Wahab, Lilawati; Mohd Isa, Haryati (2021)
Malaysia is a unique country with multi-racial society and rich with multi-layered heritage buildings which have significance on the building design, architectural qualities, craftsmanship and others. In the construction industry, building defects are a common issue related to every type of building. The same goes with the heritage buildings that have more defect problems because of the age of the building. The problem of defects needs attention to ensure the sustainability of the buildings is long lasting. In recent years, its sustainability has become a relevant issue due to the general limitation of resources and unique features of cultural heritage assets. However, it is challenging to determine the heritage building current condition during inspection and this may contribute to the asset’s failure in the future. The purpose of this paper is to get a clear understanding on the current condition and problems of heritage buildings with the main focus on the current assessment technique by the conservator in accessing defect problems for heritage buildings in Malaysia. It concludes that a pilot survey is necessary and useful in providing the groundwork in a research project. Therefore, a pilot survey has been conducted among experts in defects on heritage buildings who have more than 5 years of experience in heritage conservation work and are professionals in the field of heritage buildings in Malaysia. This paper is expected to provide some insights on building defects to the owners, consultants, contractors, conservators, various government agencies, heritage bodies and to all who are concerned with the value of heritage buildings in Malaysia.